2008
DOI: 10.1074/jbc.m800230200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Chimeras of the Phosphodiesterase 5 and 10 Tandem GAF Domains

Abstract: The tandem GAF domain of hPDE10A uses cAMP as an allosteric ligand (Gross-Langenhoff, M., Hofbauer, K., Weber, J., Schultz, A., and Schultz, J. E. (2006) J. Biol. Chem. 281, 2841-2846). We used a two-pronged approach to study how discrimination of ligand is achieved in human (h)PDE10A and how domain selection in the phosphodiesterase GAF tandems is determined. First, we examined which functional groups of cAMP are responsible for purine ring discrimination. Changes at the C-6 ring position (removal of the amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Of particular interest, generation of additional PDE5/10 chimeras demonstrated that the length-conserved linker in GAF tandems between GAF-A and GAF-B played a key role in intramolecular signaling. Swapping linkers between PDE5 and PDE10 GAF tandem domains abolished signaling (Hofbauer et al, 2008).…”
Section: Examples: Linkers Are the Vehicle For Transmission Of Informmentioning
confidence: 99%
“…Of particular interest, generation of additional PDE5/10 chimeras demonstrated that the length-conserved linker in GAF tandems between GAF-A and GAF-B played a key role in intramolecular signaling. Swapping linkers between PDE5 and PDE10 GAF tandem domains abolished signaling (Hofbauer et al, 2008).…”
Section: Examples: Linkers Are the Vehicle For Transmission Of Informmentioning
confidence: 99%
“…Human PDE5 GAF-AB domain chimeras showed significant activation by cGMP (Bruder et al, 2006). However, constructs containing either GAF-A or GAF-B PDE5 were unable to respond to cGMP stimulation (Hofbauer et al, 2008), suggesting that both GAF-A and GAF-B domains are necessary for cGMP/GAF domain PDE5 signaling.…”
mentioning
confidence: 97%